1999
DOI: 10.1016/s0735-1097(98)00607-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo targeting of acoustically reflective liposomes for intravascular and transvascular ultrasonic enhancement

Abstract: Our data demonstrate that this novel acoustic agent can provide varying targeting with different antibodies with retention of intravascular and transvascular acoustic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(137 citation statements)
references
References 21 publications
3
131
0
Order By: Relevance
“…We have demonstrated specific highlighting of atheroma with intraarterial injection of anti-intercellular adhesion molecule-1-conjugated ELIP [15], as well as targeted highlighting of a left ventricular thrombus with intravenous injection of anti-fibrinogen-conjugated ELIP [16]. We have also reported entrapment of an antibiotic and of reporter genes into these ELIP with demonstration of microbial growth inhibition and gene transfection, respectively, in cultured cells [17,18].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We have demonstrated specific highlighting of atheroma with intraarterial injection of anti-intercellular adhesion molecule-1-conjugated ELIP [15], as well as targeted highlighting of a left ventricular thrombus with intravenous injection of anti-fibrinogen-conjugated ELIP [16]. We have also reported entrapment of an antibiotic and of reporter genes into these ELIP with demonstration of microbial growth inhibition and gene transfection, respectively, in cultured cells [17,18].…”
Section: Discussionmentioning
confidence: 84%
“…We have previously reported development of echogenic liposomes (ELIP) for the targeted highlighting of structures [15,16] with potential for drug and gene delivery [17][18][19]. This study aimed to explore the potential of ELIP for thrombolytic loading, and to evaluate the effect of directed ultrasound exposure of the thrombolytic-loaded ELIP on effecting drug release and promoting thrombolysis.…”
mentioning
confidence: 99%
“…Moreover, targeting of the liposomes themselves is possible. We previously showed that echogenic liposomes conjugated to anti-ICAM-1 can be seen accumulating at early atheroma by ultrasound imaging, (Demos et al 1997;Demos et al 1999) In addition to releasing liposomal contents and providing an image of the process, ultrasound itself can have a therapeutically beneficial influence, namely facilitating access of the drug to its target through cavitation effects. For example, Porter et al found sitespecific drug delivery can be achieved by destroying drug-filled, contrast microbubbles in the target area with high-intensity US (Porter et al 1996)..…”
Section: Discussionmentioning
confidence: 99%
“…The iron oxide nanoparticles with a payload of imaging contrast agent or a drug or a combination of both, can be used for drug delivery and monitoring by images [1][2][3][4][5][6][7][8][9][10][11][12]. The iron-oxide nanoparticles bound with specific antibody also serve as a targeting system to locate the leached out antigen from the site of myocardial infarction.…”
Section: Targeted Therapeutics and Molecular Imagingmentioning
confidence: 99%
“…. The contrast mechanism of nanoparticles (liposomes or emulsions) [6][7][8], dendrimers [9,10], viral constructs [11], buckeyballs [17], or various polymers [18,19] can hold paramagnetic or superparamagnetic metals, optically active compounds (e.g., fluorescent molecules), or radionuclides. These can be detected with standard imaging equipment i.e.…”
Section: Possible Imaging Applicationsmentioning
confidence: 99%